Comparison of the behavior of fungal and plant cell wall during gastrointestinal digestion and resulting health effects: A review. (April 2021) - Colosimo, Raffaele; Warren, Frederick J.; Edwards, Cathrina H.; Ryden, Peter; Dyer, Paul S.; Finnigan, Tim J.A.; Wilde, Peter J.
Abstract: Background; The structure of many plant- and fungal-based foods is determined by cell walls which are the primary source of dietary fiber. Several studies have shown that consumption of cell wall fibers from plants and fungi can modulate digestion leading to health-promoting effects such as increasing satiety and reducing the risk of cardiovascular diseases and type-2 diabetes. Scope and Approach; We focus on the impact of the food structure determined by plant and fungal cell walls on digestion and subsequent physiological responses. The underlying mechanisms promoting health effects may differ between plant and fungal cell walls, considering their different structural and biochemical organizations. Fungal cell walls have been vastly understudied compared to plant cell walls in this regard. Therefore, we highlight differences and similarities of plant- and fungal-based foods that may underlie the observed health benefits. Key Findings and Conclusions; The ability of the plant cell walls in our diet to influence digestion and improve human health has been intensely investigated over many years. The health outcomes observed following plants and fungi consumption appear similar, despite fundamental differences between the two kingdoms of life. The possible mechanisms underlying the health effects are the control of nutrient bioaccessibility, binding and sequestration of digestive components, increasing viscosity, and colonic fermentation. Mechanisms by which cell walls influence bioaccessibility of nutrients from fungal and plant cell walls are discussed. Moreover, consistent evidence for the fungal counterpart is still lacking, and further studies focusing on the whole structure of fungi are required. Highlights: Cell walls are the main source of dietary fiber and linked to disease prevention. Cell walls from fungi and plants have different composition and structure. Similar health outcomes are linked with both plant and fungal fiber consumption. The release of digested nutrients may vary between plant and fungal cell walls. Research on fungal cell walls and health is lacking compared to those of plants.